Stimulation of Early Mathematics Concepts in Early Childhood through Balloon Number Coloring Activities - Heri Purnomo; Wahdah Zakiyatun Nisa; Abdul Halim Abdullah (Journal of Primary Education (JPE), 2026)
Mathematical learning starts in early childhood, a fundamental phase for laying the groundwork of academic concepts. This study seeks to explore the early numeracy development in young children through balloon-number coloring activities. This research used a qualitative descriptive study design in an early childhood classroom. Data were obtained from in-class observations, children’s worksheets documentation and reflective notes of the teacher during a learning activity based on the theme: “Numbers and Balloon Colors”. The results suggest that the balloon-number coloring activity engaged multiple aspects of early mathematical development, including number recognition, number–color association, symbolic thought and simple pattern recognition. While coloring, the children engaged with numerical symbols and showed interest in numbers. The findings indicate that playful and developmentally fit learning environments can significantly support the growth of early numeracy concepts when creative visual activities are activated.